Корнелій Ірод – український письменник Румунії (феномен творчості) - Носенко, Т.І. (Слово і Час, 2019)
У статті розглянуто творчість одного із чільних сучасних українських письменників Румунії –
К. Ірода. Основну увагу автор зосереджує на аналізі його роману-трилогії “Свято” (першого зразка
цієї жанрової форми в українській літературі країни), а також на науковому тлумаченні його різної
за тематично-жанровими особливостями та художньою стилістикою малої прози – оповідань, їх
своєрідного різновиду – алегорій та оповідей під назвою “промахи”. Розглядаючи основні теми
і проблеми творчості К. Ірода та особливості їх художнього потрактування, дослідниця прагне
показати своєрідність прозової спадщини письменника, з'ясувати його роль у розбудові сучасного
романного жанру та в оновленні малої прози в українській літературі Румунії. Простежено
також здобутки К. Ірода в царині художнього перекладу, передусім румунськомовні версії творів
Т. Шевченка, І. Франка, Г. Тютюнника. The essay surveys the works written by C. Irod, one of the leading contemporary Ukrainian writers
of Romania. The main attention is paid to his trilogy of novels “The Feast” and stories that vary in
thematic features and stylistics, some of them belonging to a particular type of short prose works –
allegoric pieces called “blunder stories”. Considering main themes and ideas of C. Irod’s works and
focusing on peculiarities of their literary interpretation, the researcher intends to represent the originality
of the writer’s prose heritage, to determine his role in developing the genre of the modern novel and
renovating fiash fiction in the Ukrainian literature of Romania. To achieve this aim, the researcher
adds a comparative aspect and refers to the major development patterns of the world novel of the
1960s–1980s, in particular, focusing on such a remarkable feature as ‘new epics’. The themes and
issues of the works by C. Irod have been compared to those in the works by Romanian writers, in
particular D. R. Popescu. It is noted that C. Irode’s stories have the inherent connection with the fiash
fiction of the Ukrainian masters – H. Tiutiunnyk and Ye. Hutsalo. The essay follows correspondences
in themes and literary technique that relate the Romanian writer to the mentioned Ukrainian authors.
The essay also informs about C. Irod’s achievements in the field of literary translation. In particular,
he worked over translation of T. Shevchenko’s “Diary”, as well as the book “Taras Shevchenko’s life”
by P. Zaitsev. The researcher also gives some details concerning C. Irod’s translations of the tales
“When the animals could talk” and “Mykyta the Fox” by I. Franko, the stories written by H. Tiutiunnyk
and some pieces in poetry and prose by junior Ukrainian authors.